Representação da escola no cinema um estudo sobre o filme Detachment - Silva, Carolina Cunha Da [UNIFESP] (2019)
This research aims to study the representation of the school in the movies, more specifically in Detachment, starting from the following questions: What subjects rise in this representation of the school? What relationships are prioritized: the institutional or the affective ones? The theoretical references adopted were the conceptions of cinema in the works of Walter Benjamin, Theodor Adorno and Max Horkheimer as well as the critical analysis of the society brought in their works, with the comprehension of the decline of experience as an interference of the ideology of the industrial society in the subjectivities. The method consists in the film analysis allied to the literature and documental review of the subjects in the movie. The results point that this representation of the school depictures a strong marketing bias in the school management given by the policies implemented by the reforms in the public educational system of the United States, resulting in a lack of a democratic management, the accountability, that charges the school professionals for the performance of the students by punishments and rewards and a continuing of the social and racial segregation, mainly in gentrified neighborhoods. It is possible to note a criticism upon these reforms, but aiming to redeem an ideal of democracy manifested in the Constitution of the United States, valuing the participation of the civil society; it can be seen in the main character, a substitute teacher by choice, who is not able to act in a transforming way inside the school, symbolized in the suicide of the student Meredith, but as an individual, rescues a young adolescent from the streets and the prostitution. The film prioritize the affective relationships and the emotional states of the characters who are part of the school, with a material and psychological degradation in the depicture of the teachers, as an acknowledgement of a teaching profession malaise, as well as the prioritization of the representation of the violence, through scenes of bullying, prejudicial discourses by the teachers, fights, violence against the teachers, cruelty to animals and suicide. When related to the organization of the society, these events can be seen as a consequence of the coldness of the industrial ideology, in a negligence of the affects, also in the way it thinks about education.